RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN GANYONG (Cannaedulis Kerr.) TERHADAP PERLAKUAN JENIS DAN TAKARAN PUPUK KANDANG PADA TANAH ULTISOL - Rosmiah, Rosmiah; Gusmiatun, Gusmiatun; Pebriana, Pipit (Universitas Muhammadiyah Palembang, 2014)
Response of Growth and Crop Production Canna (Canna edulis Kerr.) On treatment type and dosage of Manure on Ultisol Soil ''. Research has been carried out for 5 moon began to from May 2013 to October 2013 in the farmyard Jln. Rajawali II Lrg. Jasmine II Sekip Palembang. The research aims to determine the type and dose of the best manure on growth and yield of canna (Canna edulis Kerr). The research method used is Divided plots Design (Split plot design) with 9 combined treatment and repeated three times. Treatment main plot ie Type Manure (P) consisting of P1 = Manure Chicken Manure; P2 = Manure Cow Manure; P3 = Manure Manure Goats, while a subplot that dose of manure (T) consists of T1 = 15 tons / ha; T2 = 30 tons / ha; T3 = 45 tons / ha. Variables measured consisted of plant height (cm), number of tillers per hill, number of leaf midrib (strands), tuber weight (g) and dry berangkasan weight (g). Based on the analysis of diversity showed that treatment of chicken manure manure types, doses of manure 45 tonnes / ha and their interactions very significant effect on all observed variables. The best treatment is the type of manure chicken manure, manure dose of 45 t / ha manure and chicken manure interactions and dosing manure 45 tonnes / ha with a production of canna reach ± 42 tons / ha.